Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Bank Syariah Indonesia (Bsi) Cabang Silondae 2 - Daswan, Lestari; Lestari, Tri Desi; Hartini, Hartini (IAIN Kendari, 2024)
This research aims to test and analyze the effect of work motivation and work discipline on employee performance at bank of syariah Indonesia (BSI) in Kendari City, Southeast Sulawesi. This study used a sampling technique, namely a saturated sample totaling 18. The data collection method uses a questionnaire. The data analysis method uses multiple linear regression analysis with the help of the IBM SPSS version 20 statistical application. The results of this research show that 1. Work motivation and work discipline simultaneously have a positive effect on employee performance in BSI. 2. Work motivation partially has a significant positive effect on employee performance in BSI. 3. Work discipline partially has a significant positive effect on employee performance in BSI. The conclusion of this research is that the higher the work motivation, the greater the resulting employee performance, as well as the higher the work discipline, the greater the employee performance will be.